Impact of Domestic Water Demand Scenarios on Rainwater Harvesting System in the Andahuaylas City, Peru - Orosco, Benjamin Atao (2024)
This paper introduces a method for calculating the volume of storage tanks and analyzes demand scenarios within Rainwater Harvesting (RWH) systems. The water mass balance approach in a daily step-time was utilized to evaluate non-potable water demand across various residential rooftop areas in the city of Andahuaylas, Peru. The region is arid and experiences significant rainfall patterns during four months per year. The results demonstrated that for rooftop areas larger than 250 m2 , the demand can be fully met using commercial tanks larger than 1m3 . With system failures below 0.5%, it is possible to supply rooftop areas of 150 m2 with a volume of 5m3 . These findings highlight crucial factors to be considered during the planning and design of RWH systems in the Andean regions of Peru.